PENGGUNAAN MODEL PEMBELAJARAN TEAMS GAMES TOURNAMENT (TGT) DALAM PEMBELAJARAN IPAS UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS VI SDN KELAPA LIMA KOTA KUPANG - ceunfin, germalia ceunfin (Journal of Character and ELementary Education, 2025)
Abstract: This study aims to determine the application of the Teams Games Tournament (TGT) learning model in the material on the arrival of foreign nations to Indonesia to improve the learning outcomes of grade VI students of SDN Kelapa Lima Kupang City. This type of research is a class action research that is carried out in cycles. Each cycle consists of planning, implementation, observation, and reflection stages. The subjects of this study are 30 students with details of 17 males and 13 females. Data collection instruments are in the form of test questions and observations as supporting data. The analysis technique used is a qualitative descriptive technique. The results of this study show that the arrival of foreign nations to Indonesia using the Teams Games Tournament learning model can improve the learning outcomes of grade VI students of SDN Kelapa Lima. In the first cycle, student learning outcomes were 40% in the less category and increased to 83.33% in the second cycle whic was in the good category. So the Temas games Tournament learning model can improve student learning outcomes in the material on the arrival of foreign nations to Indonesia in grade VI of SDN Kelapa Lima Kupang City.